2012
DOI: 10.1021/es301661r
|View full text |Cite
|
Sign up to set email alerts
|

Ce–Ti Amorphous Oxides for Selective Catalytic Reduction of NO with NH3: Confirmation of Ce–O–Ti Active Sites

Abstract: The amorphous Ce-Ti mixed oxides were reported to be catalysts for selective catalytic reduction of NO(x) with NH(3), in which Ce and not Ti acts as their solvent in spite of the fact that Ce is low in content. The amorphous catalysts were characterized by X-ray powder diffraction (XRD) and transmission electron microscopy (TEM) equipped with selective area electron diffraction (SAED). The Ce-Ti amorphous oxide shows higher activity than its crystalline counterpart at lower temperatures. Moreover, the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
228
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(242 citation statements)
references
References 42 publications
9
228
0
4
Order By: Relevance
“…As shown in Figure 1, the diffraction peaks at 25.4°, 47.6° are ascribed to the characteristic reflections of anatase TiO 2 and the peak at 28.6° is ascribed to fluorite CeO 2 . There is no peak at 27.5° in the samples, which indicates that there is no rutile titania existing in all samples [17,18]. Moreover, no obvious characteristic peak assigned to a particular phase oxide is observed in 2% and 3% samples, which indicates that the amorphous phase was formed and become dominant phase in the samples [19].…”
Section: Catalytic Activity Measurementmentioning
confidence: 94%
“…As shown in Figure 1, the diffraction peaks at 25.4°, 47.6° are ascribed to the characteristic reflections of anatase TiO 2 and the peak at 28.6° is ascribed to fluorite CeO 2 . There is no peak at 27.5° in the samples, which indicates that there is no rutile titania existing in all samples [17,18]. Moreover, no obvious characteristic peak assigned to a particular phase oxide is observed in 2% and 3% samples, which indicates that the amorphous phase was formed and become dominant phase in the samples [19].…”
Section: Catalytic Activity Measurementmentioning
confidence: 94%
“…The XRD patterns of the Fe containing catalysts are compared to the W-Ce catalyst in Figure 2. [21]. Meanwhile, the peaks were not very sharp, which pointed at low crystallinity of the sample [16].…”
Section: Bet and Xrdmentioning
confidence: 96%
“…The XRD patterns of the Fe containing catalysts are compared to the W-Ce catalyst in Figure 2. All peaks of W-Ce catalyst can be assigned to cerianite (CeO 2 3 were also the dominant species [21]. Meanwhile, the peaks were not very sharp, which pointed at low crystallinity of the sample [16].…”
Section: Bet and Xrdmentioning
confidence: 97%
See 1 more Smart Citation
“…High surface area and good redox properties are important for catalytic activity, while the strong interaction between Ce and Ti and a high concentration of amorphous, or highly dispersed nanocrystalline, ceria could explain the excellent performance of the catalyst. Using various methods, Li et al [32] confirmed that the active site of a CeO2/TiO2 catalyst was the Ce-O-Ti short-range ordered species with the interaction between Ce and Ti being at the atomic level. To improve the resistance to alkali metal poisoning, a titanate nanotube in which CeO2 was confined was designed and synthesized by Chen et al [33].…”
Section: Ceria As the Main Active Component For Nh3-scr Catalystsmentioning
confidence: 99%